Binding affinities of cationic dyes in the presence of activated charcoal and anionic surfactant in the premicellar region. (28th March 2018) - Ali, Farman; Ibrahim, Muhammad; Khan, Fawad; Bibi, Iram; Shah, Syed W H
Abstract: Binding preferences of cationic dyes malachite green and methylene blue in a mixed charcoal-sodium dodecyl sulfate system have been investigated using UV-visible absorption spectroscopy. The dye adsorption shows surfactant-dependent patterns, indicating diverse modes of interactions. At low surfactant concentration, a direct binding to charcoal is preferred. Comparatively greater quantities of surfactant lead to attachment of dye-surfactant complex to charcoal through hydrophobic interactions. A simple model was employed for determination of equilibrium constant K eq and concentration of dye-surfactant ion pair N DS for both dyes. The values of binding parameters revealed that malachite green was directly adsorbed onto charcoal, whereas methylene blue was bound through surfactant monomers. The model is valid for low surfactant concentrations in the premicellar region. These findings have significance for material and environmental sciences.